COMMUNITY PARTICIPATION IN THE ACTION PLAN GREEN CITY - Oktarizka Reviandani; Vidya Imanuari Pertiwi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Green City is one of the adaptation strategies that are responsive to the impacts of climate change. A green city is a city development concept that emphasizes sustainable aspects. The placement of sustainable development as the basic principle of the Green City Concept furthermore demands the participation of the community. The purpose of this study was to describe and analyze community participation in the Green City Action Plan in Surabaya City as well as the supporting and inhibiting factors of community participation in the Green City Action Plan in Surabaya City. This study uses a descriptive research method with a qualitative approach, as well as an interactive model of qualitative data analysis. The results show that the process of community participation can be formed because of the opportunity, ability, and willingness of the community to participate. The degree of community participation is in the degree of participation. The willingness of the community and the commitment of the Central Government to support participation are supporting factors. Meanwhile, the community's dependence on the government and management that has not been optimal is a factor inhibiting participation.